Strategi Pengemasan Wisata Trekking Di Hutan Pinus Wonoasih, Kabupaten Banyuwangi - Putri Septaria; Made Sukana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
The tourism development in Indonesia has increase rapidly,as the statistical data shows that the number of foreign tourist visits Indonesia in June 2018 escalate 15.21 percent compared to June 2017, specifically from 1.14 million visits up to 1.32 million visits. Indonesia are improving their tourism sector, for example the Banyuwangi City. One of the tourist attractions with its natural potential is Wonoasih Pine Forest., lot of activities that can be packaged into tourism attractions.This study used qualitative approach method, qualitative and quantitative data obtained directly by observation, interview and documentation, and data analysis techniques in this study used SWOTanalysis which is a qualitative analysis tool that is done by examining internal and external factors.By using SWOT analysis, four strategies are produced in the packaged of trekking tourism activities, specifically: (1) SO strategy which contains the design of trekking tourism products and opening up jobs, (2) WO strategy which contains institutional development and tourism human resources, (3) ST strategy which contains increased security, enchance accident insurance and regulations on maintaining natural surroundings and cleanliness, and (4) WT strategy which contains market penetration and promotion of trekking tours as well as routine socialization of destination branding. Keyword: Packaging Strategy, Trekking, SWOT Analysis, Wonoasih Pine Forest